Sleep quality and fatigue among hemodialysis patients - Hayfa Almutary; Simar Alghamdi; Aisha Mezan; Hanaa Farsi; Abeer Alsayegh; Afnan Alqurashi; Ruba Alharazi (International Journal of Noncommunicable Diseases)
Background: Sleep quality is a crucial clinical outcome for hemodialysis (HD) patients, and fatigue is among the most prevalent symptoms experienced by this group. However, research on sleep quality and fatigue among HD patients in Saudi Arabia remains relatively scarce. Aims: The study aimed to evaluate the quality of sleep and fatigue levels among HD patients and to examine the correlation between these two variables. Methods: This study employed a cross-sectional design with a convenience sample of 96 HD patients. Data were collected from two large public hospitals using the Fatigue Severity Scale and the Pittsburgh Sleep Quality Index (PSQI). Results: The findings revealed that the global PSQI score was 7.93 ± 3.63, indicating moderate sleep disturbance, while fatigue levels were also moderate, with a mean of 4.60 ± 1.76. A moderate positive and significant correlation was observed between fatigue and poor sleep quality. When comparing individuals with poor sleep (PSQI ≥ 5) to those with good sleep (PSQI < 5), poor sleepers exhibited significantly higher fatigue levels (mean = 4.89) than good sleepers (mean = 3.5, P = 0.001). No significant differences were identified in other clinical or demographic factors. Conclusions: This study highlights the high prevalence of poor sleep quality and fatigue among HD patients, underlining the importance of addressing these issues to improve patient outcomes. Further research is needed to explore the underlying causes of sleep disturbances and fatigue in this population and to evaluate interventions that can help improve sleep and reduce fatigue, ultimately enhancing the quality of life for these patients.